Optimal Power Flow of Renewable-Integrated Power Systems Using a Gaussian Bare-Bones Levy-Flight Firefly Algorithm - Alghamdi, Ali S. (Frontiers in Energy Research, 2022)
This article proposes a Gaussian bare-bones Levy-flight firefly algorithm (GBLFA) and its modified version named MGBLFA for optimizing the various kinds of OPF problems in the presence of conventional thermal power generators and intermittent renewable energy resources such as solar photovoltaic (PV) and wind power (WE). Several objective functions including fuel costs, emission, power loss, and voltage deviation are considered in the OPF problem subject to the economical, technical, and safety constraints. Also, the uncertainties of solar irradiance and wind speed are modeled using Weibull and lognormal probability distribution functions and their influences are considered in the OPF problem, and proper cost functions associated to the power generation of PV and WE units are modeled. A comprehensive analysis in the form of ten cases with various objectives on the IEEE 30-bus test system demonstrate the potential effects of renewable energies on the optimal scheduling of thermal power plants in a cost-emission-effective manner. Also, the simulation results illustrate the effectiveness and validity of the GBLFA and MGBLFA algorithms in compared to other recently published algorithms for solving OPF problems.